State, society and information technology in Asia alterity between online and offline politics - Chong, Alan; Yahya, Faizal (Ashgate Pub., 2014)
Calling attention to the unique social and political uses being made of IT in Asia, in the service of offline and online causes predominantly filtered by pre-existing social milieus.